Regional Differentiation and National Uniformity: Norwegian Elementary School Legislation in the Eighteenth and Early Nineteenth Century - Tone Skinningsrud; Randi Skjelmo (Nordic Journal of Educational History, 2016)
Previous research on Norwegian educational reforms after 1814, the year when Norway became a constitutional state, has emphasized the conservatism of the elementary education acts of 1816 and 1827. Contrary to expectations for a constitutional state, these acts did not reflect a concern for fostering politically active citizens. Neither did they follow up the enlightenment idea of teaching secular knowledge to the common people. We raise a new question concerning post-1814 educational legislation in Norway: was there an increased emphasis on national uniformity after 1814? A close reading of the earlier 1739/41 acts and the 1827 act, including the Plan and Instruction from 1834, studies of the debates in the Norwegian Parliament 1815–1827 and the temporary 1816 act on elementary education, show that policy after 1814 emphasised national uniformity more than before. Despite continued local funding of elementary schooling, national policy and legislation promoted uniformity.